Potential areas of evergreen forests in Castile and Leon (Spain) according to future climate change - Del Río, Sara; ngel Penas, Á (Phytocoenologia, 2006)
Areas that may potentially be occupied by evergreen forests represent approximately 47% of the total area of the Castile and Leon region. This type of vegetation includes holm-oak (Quercus rotundifolia) and white juniper (Juniperus thurifera) forests. Both of them belong to eight different vegetation series.Considering the observed trends in annual mean temperature and precipitation in Castile and Leon for a thirty-seven-year period (1961?1997), three different hypotheses are put forward in this work to account for climate variations over periods of 25, 50 and 75 years and thus determine the changes that might occur in the areas suited to occupation by evergreen forests.This study also emphasizes the relevance of bioclimatic models for anticipating possible changes in the potential natural vegetation of a territory because of the influence of these changes on land use, conservation and management.Overall, our data support the concept that a decrease in Quercus rotundifolia and Juniperus thurifera forests could occur in Castile and Leon in the near future if the temperature and precipitation trends observed during recent years would remain constant. The main trends indicate an increase in the temperature of winter and decreases in summer. As far as precipitation is concerned, there is an increase in summer and decreases in winter. We conclude that these types of forest may be replaced by deciduous formations.
Keywords: bioclimatology; climactic dominion; climate change; evergreen forests